2019
DOI: 10.1002/slct.201901391
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Activity and 3D‐QSAR Study of Hybrid Oxazine Clubbed Pyridine Scaffolds

Abstract: Compounds1-((1-(4-(2H-benzo[e] [1,3]oxazin-3(4H)-yl)phenyl) ethylidene)amino)-6-((arylidene)amino)-4-(4-chlorophenyl)-2oxo-1,2-dihydropyridine-3,5-dicarbonitriles (4a-j) were prepared, characterized and screened for antimicrobial activity. 3D-quantitative structure activity relationship (3D-QSAR) was explained by CoMFA and CoMSIA models to rationalize the antimicrobial activity of the titled compounds. Statistically significant 3D-QSAR (CoMFA and CoMSIA) models were created which could provide valuable informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Various pyridine containing anti-inflammatory and antimicrobial agents are also reported in the literature. Researchers like Fan et al , 23 Bhila et al , 24 Desai et al , 25 Rani and Reddy, 26 and Rashdan et al ( 27 ) reported some antimicrobial agents. Laddha and Bhatnagar, 28 Kumar et al , 29 and Thirumurugan et al ( 30 ) reported some pyridine-based anti-inflammatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…Various pyridine containing anti-inflammatory and antimicrobial agents are also reported in the literature. Researchers like Fan et al , 23 Bhila et al , 24 Desai et al , 25 Rani and Reddy, 26 and Rashdan et al ( 27 ) reported some antimicrobial agents. Laddha and Bhatnagar, 28 Kumar et al , 29 and Thirumurugan et al ( 30 ) reported some pyridine-based anti-inflammatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…Desai et al [ 13 ] have studied the in vitro antimicrobial activities of some newly hybrid oxazino-pyridine derivatives. The desired compounds, oxazin-3(4 H )-yl)phenyl)ethyildene)amino)-6-((arylidene)amino)-4-(4-chlorophenyl)-2-oxo-1,2-dihydropyridine 23a – j , were synthesized in two steps, by cyclocondensation of oxazine 21 followed by condensation of the intermediate 22 , Scheme 5 .…”
Section: Resultsmentioning
confidence: 99%
“…CoMFA and CoMSIA methods were used for 3D-QSAR analysis [19], and all operations were completed with SYBYL2.1.1 software module. The molecular dynamics program Minimize was used to optimize the energy of all compounds to obtain their lowest energy conformation.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In the quantitative structure-activity relationship modeling, the biological activity value LD50 (collected from PubChem) was calculated in mg/kg, as shown in Table 1. CoMFA and CoMSIA methods were used for 3D-QSAR analysis [19], and all operations were completed with SYBYL2.1.1 software module. The molecular dynamics program Minimize was used to optimize the energy of all compounds to obtain their lowest energy conformation.…”
Section: D-qsarmentioning
confidence: 99%